TANAH DALAM PERSPEKTIF FILSAFAT ILMU HUKUM - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This article overviews the values that underlie land control and ownership regulations. There are three value systems: communal, individual and Islam. Indonesia develops communal system by still accommodating individual system perspective. However, Indonesia is trapped into liberalism/capitalism idea in which land is seen as commodity.